Profil Kekerasan Orangtua pada Anak di Desa Tanjung Kecamatan Bathin VIII Kabupaten Sarolangun - Khairina, Silvi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the description of physical and psychological violence of parents on children in Tanjung Village, Bathin VIII District, Sarolangun Regency. Based on observations and interviews conducted by researchers, it turns out that there are still parents who commit physical and psychological violence on children, therefore children get trauma such as children who are afraid of their parents, children who like to bemoody, children who lack self-confidence or feel inferior. towards their friends, the existence of children who like to be nosy towards their friends, and the loss of the child's ability to act. The focus of this research is (1) Profile of physical violence of parents on children, (2) Profile of psychological violence of parents on children. The type of research used is descriptive qualitative research that describes the causes, facts and realities thatexist in the field. The informants in this study were chosen randomly (arbitrarily or without a pattern), while the key informants were 2 pairs of parents, and the supporting informants were 6 elementary school age children in Tanjung Village, Bathin VIII District, Sarolangun Regency, and 2 neighbors. This research data collection using interviews and observation. This data was tested by triangulation, after that it was analyzed using 3 stages, namely; (1) Data reduction, (2) Data presentation, (3) Drawing conclusions. The results showed that;(1) The profile of parental physical violence, namely hitting, pinching, twisting, pushing, and shaking the child's body (2) The profile of parental psychological violence against children, namely yelling, ignoring, belittling, comparing children with their friends, and even threatening children.